2017
DOI: 10.21548/26-2-2129
|View full text |Cite
|
Sign up to set email alerts
|

Cover crop management in a Sauvignon blanc/Ramsey vineyard in the semiarid Olifants River Valley, South Africa. 1. Effect of management practices on selected grass and broadleaf species

Abstract: This trial was conducted over a period of ten years on a sandy soil in a Sauvignon blanc/Ramsey vineyard in Lutzville (31°35'S, 18°52'E), situated in the semi-arid Olifants River Valley of the Western Cape. Twenty-three treatments were applied. Eight cover crop species that received the same amount of fertilizer were controlled chemically at the end of August or at the end of November. Two treatments were also applied in which Avena sativa L. v. Saia ('Saia' oats) and Vicia dasycarpa Ten. (grazing vetch) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 10 publications
3
27
0
Order By: Relevance
“…The use of cover crops in vineyards reduces water runoff and erosion (Louw & Bennie, 1992) restricts evaporation from the soil surface (Van Huyssteen et al, 1984), conserves soil water (Buckerfield & Webster, 1996), and reduces temperature fluctuations in the soil (Van Huyssteen et al, 1984). It is also a non-specific method of pre-emergence weed control (Fourie et al, 2001;Van Huyssteen et al, 1984) and has the ability to suppress both winter-and summer-growing weeds (Fourie et al, 2005;Fourie et al, 2006). Van Huyssteen and Weber (1980) found that grape production and pruning mass were significantly affected by the soil cultivation practice applied in a non-irrigated Chenin blanc vineyard established on a medium textured soil.…”
mentioning
confidence: 99%
“…The use of cover crops in vineyards reduces water runoff and erosion (Louw & Bennie, 1992) restricts evaporation from the soil surface (Van Huyssteen et al, 1984), conserves soil water (Buckerfield & Webster, 1996), and reduces temperature fluctuations in the soil (Van Huyssteen et al, 1984). It is also a non-specific method of pre-emergence weed control (Fourie et al, 2001;Van Huyssteen et al, 1984) and has the ability to suppress both winter-and summer-growing weeds (Fourie et al, 2005;Fourie et al, 2006). Van Huyssteen and Weber (1980) found that grape production and pruning mass were significantly affected by the soil cultivation practice applied in a non-irrigated Chenin blanc vineyard established on a medium textured soil.…”
mentioning
confidence: 99%
“…The use of cover crops, which is standard practice in South African vineyards, has many advantages, including the reduction of water run-off and erosion (Khan et al, 1986;Roth et al, 1988;Louw & Bennie, 1992), the preservation of soil moisture (Buckerfield & Webster, 1996), the reduction of evaporation from the soil (Myburgh, 1998), temperature regulation of the soil (Fourie & Freitag, 2010), the improvement of soil organic matter (Fourie et al, 2007;Fourie, 2012) and the suppression of weeds (Fourie et al, 2005(Fourie et al, , 2006Fourie, 2010). The choice of cover crop is determined by the edaphic conditions that are prevalent in the different grapevine regions, as well as by the requirements of the grapevines concerned (Fourie et al, 2001).…”
Section: Figure 2 Slashing Of Crops With Slasher (A) Texture Of Slasmentioning
confidence: 99%
“…Effective weed control can be achieved by using grain and broadleaf annuals as cover crops for the biological control of weeds in the vineyards and orchards of South Africa (Fourie, 2005;Fourie et al, 2005;2006;Fourie, 2010;Fourie et al, 2015). Facelli and Pickett (1991), as well as Shrestha et al (2002), observed that the type of plant residue cover affected the weed species composition.…”
Section: Introductionmentioning
confidence: 99%